The Influence of Inflation, Unemployment, and Human Development Index on Economic Growth in Indonesia from an Islamic Economic Perspective - Luthfi Nur Rosyidi; Muhammad Wahyu Haidar Rahman (Universitas Islam KH. Achmad Muzakki Syah Jember, 2026)
Economic growth remains a key indicator of national development; however, its sustainability is closely influenced by macroeconomic stability and the quality of human resources. High inflation and unemployment can hinder economic performance, while improvements in the Human Development Index (HDI) may strengthen long-term growth capacity. Therefore, this study aims to examine the effects of inflation, unemployment, and HDI on Indonesia’s economic growth during the 1994–2023 period and to interpret the findings from an Islamic economic perspective. This research employs a quantitative approach using annual time-series data obtained from the World Bank and the United Nations Development Programme (UNDP). Data were analyzed using the Error Correction Model (ECM) with EViews 12 to capture both short-run and long-run relationships among variables. The results indicate that inflation, unemployment, and HDI jointly explain 99.07% of the variation in economic growth in the long run. Partially, inflation and unemployment exert significant negative effects on economic growth, whereas HDI has a significant positive effect in both the short and long run. Furthermore, the error correction term (ECT = −0.318) confirms a stable adjustment mechanism, indicating that deviations from long-run equilibrium are corrected at a speed of 31.8% per year, with equilibrium restored within approximately three years. From an Islamic economic perspective, these findings support the objectives of maqashid al-shariah, particularly the protection of wealth (hifdz al-mal), life (hifdz al-nafs), and intellect (hifdz al-aql). The study concludes that sustainable economic growth requires not only output expansion but also price stability, employment creation, and continuous improvement in human development.